Comparing novel sperm extenders for the internally-fertilizing tiger salamander (Ambystoma tigrinum) - Chen, Devin M.; Kouba, Carrie K.; Songsasen, Nucharin; Roth, Terri L.; Allen, Peter J.; Kouba, Andrew J. (Frontiers in Amphibian and Reptile Science, 2024)
Due to the concentrated nature and small volume of spermic milt that is typically produced from internally-fertilizing salamanders, an extender is needed to analyze the sperm for quality and quantity metrics. Techniques for diluting salamander sperm for analysis have thus far utilized low osmolality media, which are likely physiologically distinct from the salamander female reproductive tract. Application of mammalian sperm extenders could maintain salamander sperm motility and morphology in storage longer due to the similar nature of internal fertilization in both taxa. Several sperm extenders were tested including: Multipurpose Handling Medium, Sperm Washing Medium, Modified Ham’s F-10 Basal Medium (HAM’s), Refrigeration Medium, and 10% Holtfreter’s solution as a control. The experimental treatments were divided into two groups: diluted (90 mOsm, the approximate osmolality of salamander sperm) and undiluted (280-320 mOsm). Milt samples were collected from male tiger salamanders (N=11) and diluted 1:50 with each of the treatments and measured for sperm progressive motility, total motility, and normal morphology every 10 minutes for one hour. When comparing the diluted versus undiluted treatments of the same extender, there was no difference (p>0.05) for any of the response variables. In addition, we found that 10% Holtfreter’s solution is best for maintaining progressive motility, while diluted HAM’s is best for retaining total motility and normal morphology over time. Overall, we found that osmolality is not a key driver influencing tiger salamander sperm motility, but rather other factors such as ionic composition or pH could be affecting sperm form and function.